Neutralizing antibody-dependent and -independent immune responses against SARS-CoV-2 in cynomolgus macaques - Ishigaki, Hirohito; Nakayama, Misako; Kitagawa, Yoshinori; Nguyen, Cong Thanh; Hayashi, Kaori; Shiohara, Masanori; Gotoh, Bin; Itoh, Yasushi (Virology (New York, N.Y.), 2021)
We examined the pathogenicity of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in cynomolgus macaques for 28 days to establish an animal model of COVID-19 for the development of vaccines and antiviral drugs. Cynomolgus macaques infected with SARS-CoV-2 showed body temperature rises and X-ray radiographic pneumonia without life-threatening clinical signs of disease. A neutralizing antibody against SARS-CoV-2 and T-lymphocytes producing interferon (IFN)-γ specifically for SARS-CoV-2 N-protein were detected on day 14 in one of three macaques with viral pneumonia. In the other two macaques, in which a neutralizing antibody was not detected, T-lymphocytes producing IFN-γ specifically for SARS-CoV-2 N protein increased on day 7 to day 14, suggesting that not only a neutralizing antibody but also cellular immunity has a role in the elimination of SARS-CoV-2. Thus, because of similar symptoms to approximately 80% of patients, cynomolgus macaques are appropriate to extrapolate the efficacy of vaccines and antiviral drugs for humans. •Cynomolgus macaques infected with SARS-CoV-2 showed fever.•SARS-CoV-2 caused X-ray radiographic and histological pneumonia in cynomolgus macaques.•A thrombus was found in cynomolgus macaques infected with SARS-CoV-2.•A neutralizing antibody against SARS-CoV-2 were detected in one of three macaques.•T-lymphocytes producing IFN-γ specifically for SARS-CoV-2 increased in infected macaques.